THE RELATIONSHIP BETWEEN COMMUNITY RESOURCES AND RELIGIOUS SPIRITUAL COPING WITH COPING STRATEGIES IN CAREGIVER ADAPTATION FOR POST-STROKE FAMILY MEMBERS IN KOTAMOBAGU CITY, INDONESIA - Ake Royke Calvin Langingi; Grace Ireine Viodyta Watung; Pagayang, Zefania Ireyne (PT. Jurnal Center Indonesia Publisher, 2025)
Stroke is a condition in which brain function is rapidly disrupted and lasts for more than 24 hours due to an interruption of blood flow to the brain. Globally, the incidence and morbidity rates of stroke continue to increase. The quality of life of acute and chronic stroke patients is influenced by post-stroke depression. Community resources (CR) and spiritual religious coping (SRC) factors are also related to the coping adaptation strategies of family caregivers for members who have experienced a stroke. Patients who experience post-stroke depression show a lower quality of life one year after stroke compared to those who do not experience it. This study is a quantitative research with an observational study design. The study was conducted from January to March 2024 in Kotamobagu City. The total population of stroke patients distributed across seven community health centers in Tomohon City is 200 patients. The sample was taken using total sampling method consisting of 200 family caregivers. The results were then analyzed using the Chi Square test with SPSS. All variables were significantly related to the coping adaptation strategies of family caregivers for members who had a stroke. Community resources (CR) were significantly related to caregiver coping strategies (p = 0.025), and spiritual religious coping (SRC) was also significantly related to coping strategies (p = 0.032). Community resources and spiritual religious coping among family caregivers of post-stroke patients are needed to increase motivation and reduce caregiver stress..